KETERKAITAN AMERIKA SERIKAT DENGAN TUDUHAN PENDANAAN TERORISME OLEH QATAR8 - Novi Rizka Amalia (Dauliyah Journal of Islamic and International Affairs, 2018)
The allegation against Qatar for its link with terrorist financing has resulted in the country incorporated in the Gulf Cooperation Countries (GCC) regional organization being excluded from its membership in the organization. Qatar is considered to have violated the agreement in the organization because it has received a Muslim Brotherhood that is con-sidered to threaten and disrupt the stability of the Gulf region’s security. In the case of this diplomatic termination, Saudi Arabia became the main control holder. But as we know that Saudi Arabia is a neighboring coun-try that has good relations with Qatar. So that allegedly there is a linkage of the United States in this country’s Gulf of diplomatic conflicts. This is based on the inconsistency of the united states in action. Qatar is cele-brating one of America’s largest trading partners in military supplies, but precisely the United States’s president trump, strongly opposed to Qatar’s unproven crime. So with the qualitative method, this paper will discuss the involvement of the united states in Qatar’s alleged terrorism financing in terms of national interest achievement.